The Oxford handbook of the economics of food consumption and policy - Lusk, Jayson; Roosen, Jutta; Shogren, Jason F. (Oxford : Oxford University Press, 2011)
This handbook brings together contributions from the top researchers in the economics of food consumption and policy. Designed as a comprehensive guide to academics and graduate students, it discusses theory and methods, policy, and current topics and applications.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Food consumption -- Economic aspects; Food consumption -- Government policy